FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR NELAYAN KABUPATEN KONAWE SULAWESI TENGGARA - Irdam Riani; Ashar Bafadal; Rahmat Sofyan Patadjai (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
Exchange rate of farmers (NTN) can depict term of trade of the farmers from a farming conserning the need of produktion faktors and consumption on products or services. This research aims to studi same faktors significantly influencing end studi elasticity the  NTN of farmers in Konawe District. The regretiossion analysis result show that production, seeds weight, the amount of fuels, stretch of ropes, the amount of sugar and cigarette consumptionnymber of dependents, weather and tribes are all obviously influencing the NTN of seaweed in Konawe.  Partially faktors that correlate positively and influence signifikcantly with the NTN of seaweed are production, seeds wiight, and streatch of ropes, whereas the amount of fuels and comsumption  of sugar are negetifly correlated but obviously influential.  Some variabeles seem not real influencing to the NTN such as cigarette comsumption, the number of dependents, weather and the tribes.  Based on elasticity analysis, the NTN will increase as 62% if the farmers can increase 100% of production, then in increase as 15% if the seeds weight are lifted to 100%, and will increase as 11,6% if the stretch of ropes is added to 100%.  Additionaly, the NTN wil decrease as 23% if the use fuels rises  100% and will decrease as 12% if the sugar consumption increase as much as 100%Keywords : Exchange Rate Farmers, Farmers See Grass, Signifikcant, Elasticity